2006
DOI: 10.1111/j.1365-3164.2006.00513.x
|View full text |Cite
|
Sign up to set email alerts
|

Histological and genotypical characterization of feline cutaneous mycobacteriosis: a retrospective study of formalin‐fixed paraffin‐embedded tissues

Abstract: Twenty-nine cases presumptively diagnosed as feline cutaneous mycobacteriosis were evaluated microscopically with haematoxylin and eosin and modified Fite's stained sections using archived formalin-fixed paraffin-embedded tissue specimens. Lesions were characterized histologically as feline leprosy (7 cases lepromatous and 16 cases tuberculoid) or atypical mycobacteriosis (3 cases); three cases did not fit these criteria and were classified as 'miscellaneous'. Actinomycetales-specific polymerase chain reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 25 publications
3
54
1
2
Order By: Relevance
“…Cats are an excellent sentinel species for environmentally acquired infections, as they have a finite geographical range (4,20). It is therefore highly likely that Mycobacterium sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cats are an excellent sentinel species for environmentally acquired infections, as they have a finite geographical range (4,20). It is therefore highly likely that Mycobacterium sp.…”
Section: Discussionmentioning
confidence: 99%
“…With one exception, culture from all Australian feline leprosy cases had been unsuccessful, de-spite the use of a range of appropriate media and the presence of abundant AFB in most specimens. Recent work from North America has indicated that additional, closely related mycobacterial taxa (belonging to a species provisionally called "M. visibilis"; later corrected to "M. visibile") also cause disseminated skin disease in cats (2,4,8).…”
mentioning
confidence: 99%
“…[9][10][11][12][13] Cases occur worldwide, although certain mycobacterial species have strong geographical predilections. Critically, FLS lesions cannot be distinguished clinically or microscopically from lesions caused by tuberculosis bacteria (Mycobacterium bovis and Mycobacterium microti) and members of Mycobacterium avium complex (MAC).…”
Section: Feline Leprosy Syndromesmentioning
confidence: 99%
“…Canine leproid granuloma (CLG) [1][2][3][4][5][6][7][8] and the feline leprosy syndromes (FLS) [9][10][11][12][13] are relatively uncommon nodular dermatoses caused by species of saprophytic mycobacteria that are extremely fastidious and generally uncultivable in the laboratory. Infection may be self-limiting, particularly in dogs with CLG, 2 although it is impossible to predict which cases will have lesions that regress spontaneously.…”
Section: Introductionmentioning
confidence: 99%
“…8,19 Antemortem diagnosis of M. bovis infection within cattle uses the tuberculin skin test, the single intradermal comparative tuberculin test, and the gamma interferon assay; however, skin testing is reportedly inconsistent when used in domestic cats. 4,5,11,13,14,19,24 In an effort to increase sensitivity and specificity in antemortem assays, laboratories have expanded their research to include both cellmediated and humoral immune responses with diagnostic tests such as enzyme-linked immunosorbent assay (ELISA), multiple antigen print immunoassay (MAPIA), and rapid test. The most recent immunodiagnostic tests developed for cats are the gamma interferon (IFN-c) ELISA and enzymelinked immunospot (ELISPOT) assay.…”
Section: Introductionmentioning
confidence: 99%